Doporučené postupy a trendy v imunosupresivní léčbě glomerulonefritid podle KDIGO (Clinical Practice Guideline for Glomerulonephritis) - Podracká, L; Matoušovic, K (Vnitrni lekarstvi, 2013)
We summarize recommendations for glomerulonephritis treatment, established by internationally recognized experts in the field and sponsored by KDIGO (Kidney Disease Improving Global Outcomes). Up till now, the KDIGO review has been the most prestigious analysis of therapeutic trials on immunosuppressive treatment of glomerulonephritides. The 167 recommendations addresses the following forms of glomerulopathies: steroid-sensitive nephrotic syndrome and steroid resistant nephrotic syndrome in children; minimal change disease and idiopathic focal segmental glomerulosclerosis in children and adults; idiopathic membranous nephropathy; idiopathic membranoproliferative glomerulonephritis; glomerulonephritis associated with infection; immunoglobulin A nephropathy and Henoch-Schönlein purpura nephritis; lupus nephritis; pauci-immune focal and segmental necrotizing glomerulonephritis; and anti--glomerular basement membrane antibody glomerulonephritis. We focused our attention on progress in this topic in the last decade.
Keywords: směrnice pro lékařskou praxi jako téma; Glomerulonephritis; Adult; dospělí; glomerulonefritida; Immunosuppressive Agents; Humans; Practice Guidelines as Topic; lidé; imunosupresiva